Reporte tipológico y cronológico de los componentes cerámicos de Cerro Cebollal (LP-134), La Pintada, provincia de Coclé - Sánchez Herrera, Luis Alberto (Revista Española de Antropología Americana, 2007)
In LP-134 site was found some remains of Monagrillo pottery (3000-1200 B.C.), similars to remains located in other archaeological sites of «Gran Coclé» cultural region. In our research we have used the traditional methodology for pottery analysis, but for the complexity of the vertical register of this site, we have done a tracking of the movements of each share and of each tipological category, along the vertical record, in order to reconstruct the occupational history of this site. In this report we suggest that the oldest occupation of the deposits is represented by the Monagrillo pottery and a group with plastic decorations. Then took place some mining activities and the site was eventually used for burial.